ANALISIS PENGARUH DIMENSI KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN (Studi Kasus Pada Konsumen Swalayan Sentral kendal) - ARDIANTO, 08.05.51.0087 RIFQI; Suharmanto, Toto (Students Journal of Economic and Management, 2012)
Research with the title âANALYSIS OF INFLUENCE OF QUALITY SERVICE CUSTOMER SATISFACTION â.(Studies in Self-Service Consumer Sentral Kendal), aims to analyze the customer satisfaction department of the Sentral Kendal.The population in this study were the Sentral Kendal supermarket consumers who shop at the site. Determination of the sample is done by techniques âAccidental samplingâ, The sampling technique based on the accident and the number of samples taken by as many as 100 persons / respondents. The collected data were analyzed using the following: factor analysis to test the validity of the statement items, Cronbach Alpha formula to test the reliability of the instrument, the regression analysis to examine the magnitude of the effect of each independent variable on the dependent variable and the coefficient of determination and F test used to test the goodness of the model (Goodness of Fit). Based on data analysis and hypothesis test obtained that is partially the result of physical evidence variable, reliability, responsiveness, assurance, and empathy has a positive and significant impact on customer satisfaction. Variable physical evidence, reliability, responsiveness, assurance, and empathy together have a positive and significant impact on customer satisfaction. The most influential variables are dominant to the satisfaction of the members of the five variables are the physical evidence. The test result is known that the variable coefficient of determination of physical evidence, reliability, responsiveness, assurance, and empathy are able to explain the variation of 78.5% to the satisfaction of the Sentral department customer kendal, while the rest of 21.5% influenced by other variables not included in this study.Key words: Tangible, Reliability, Responsiveness, Assurance, Emphaty, Customer Satisfaction.